2013
DOI: 10.1364/ol.38.002020
|View full text |Cite
|
Sign up to set email alerts
|

Splitting of levels in a cylindrical dielectric waveguide

Abstract: A splitting of modes in a circular graded-index optical fiber is demonstrated by solving the full Maxwell equations using the perturbation analysis. It is shown that the degeneracy of vortex Laguerre-Gauss modes with distinct orbital angular momentum (OAM) and polarization (spin) but the same total angular momentum is lifted due to the spin-orbit (vector) and tensor forces. Numerical estimations of group delays of modes in optical fiber and frequency splitting in Fabry-Perot and ring resonators are presented.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 14 publications
0
20
0
Order By: Relevance
“…The slowing down of the light propagation velocity in waveguides is well known and can be explained by the delays of modes. In 41 , it is shown that at this delay also depends on the magnitude of the orbital angular momentum (helicity of the wave front) and the spin angular momentum (polarization) of the propagating beam. Therefore, it can be assumed that a polarization similar to the orbital angular momentum will affect the propagation velocity in the free space of pulsed beams with OAM and SAM.…”
Section: Discussionmentioning
confidence: 99%
“…The slowing down of the light propagation velocity in waveguides is well known and can be explained by the delays of modes. In 41 , it is shown that at this delay also depends on the magnitude of the orbital angular momentum (helicity of the wave front) and the spin angular momentum (polarization) of the propagating beam. Therefore, it can be assumed that a polarization similar to the orbital angular momentum will affect the propagation velocity in the free space of pulsed beams with OAM and SAM.…”
Section: Discussionmentioning
confidence: 99%
“…There is no mode conversion at propagation if the incident beam is expressed by (4). Note that the hybrid wave function (4) The propagation constant correct to first-order nonparaxial term is given by [20]:…”
Section:   Imentioning
confidence: 99%
“…The propagation constant correct to first-order non-paraxial term of the Hamiltonian is given by [21]: (9) where η = ω/ .…”
Section: Modelmentioning
confidence: 99%